Selenium - its role in physiology and endocrinology and as organoselenium compounds in oncology: A minireview - Brtko Julius; Podoba Jan; Macejova Dana (Endocrine Regulations)
The present minireview traces the road leading to discovery of selenium, formerly appointed as a toxic element that became later a bioelement, which is necessary for the proper functioning of living organisms. Selenium occurs in human and animal bodies either in the form of seleno-Lcysteine or its dimeric form seleno-L-cystine as a crucial component of selenoenzymes or selenoproteins. Selenium atom represents an integral component of the enzyme active site of different forms of glutathione peroxidase, which catalyzes conversion of hydrogen peroxide and organic hydroperoxides into the water and corresponding alcohols. A revolutionary breakthrough in the field of endocrinology came with the identification of different forms of iodothyronine deiodinase as selenoenzymes, which play an important role in the metabolism of thyroid hormone. The role of selenium in immune function and autoimmune thyropathies that might be associated with selenium deficiency are reported and discussed. This minireview also brings forward novel directions of organoselenium compounds or selenium nanoparticles in cancer therapy. Based on the update of available literature and the author’s experimental experience, the minireview can be devoted to clinicians and medical students.